MRI characteristics of sporadic CJD with valine homozygosity at codon 129 of the prion protein gene and PrPSc type 2 in Japan. Issue 3 (13th February 2004) - Fukushima, R; Shiga, Y; Nakamura, M; Fujimori, J; Kitamoto, T; Yoshida, Y
Abstract : Two Japanese sporadic Creutzfeld-Jakob disease (sCJD) patients with valine homozygosity at codon 129 of the prion protein gene and protease-resistant prion protein (PrP Sc ) type 2 (VV2) are described. In contrast with Western countries, this type of sCJD is very rare in Japan. In 123 sCJD cases, only two were recognised as VV2 by the Japanese CJD surveillance committee. The clinical symptoms and pathological findings of the patients were similar to those of European and US patients. The noteworthy finding of diffusion weighted MRI (DWI) was that an abnormal high intensity covered a wide range of the thalamus including the dorsomedial nucleus, the pulvinar, and the ventral anterior, lateral, and posterolateral nuclei. This thalamic pattern has not been recognised in sCJD with methionine homozygosity and PrP Sc type 1 (MM1) or methionine/valine heterozygosity and PrP Sc type 1 (MV1) which comprises the vast majority of sCJD. This finding may be characteristic to VV2 and may distinguish it from MM1, MV1, and variant CJD. DWI can provide a very important clue for the antemortem diagnosis of VV2 subjects.